Gas-geochemical studies of gas fields and increased metal concentrations in the East Siberian Sea - B., Shakirov R.; Sorochinskaja, A. V.; Syrbu, N. S.; Tsunogai, Urumu; Yen, Tran Hoang (Vietnam Journal of Earth Sciences, 2020)
Paper presents the results of complex gas-geochemical studies of bottom sediments of the East Siberian Sea along the meridional profile from Cape Billings to the Mendeleev Ridge. Abnormal concentrations of methane (up to 2.4% vol.) and hydrogen (up to 600 ppm) are controlled by neotectonic faults and are typical for the areas of gas hydrate formation. The carbon isotope composition indicates the predominance of the thermogenic component. When studying the chemical composition of sediments, the data helped to identify the permeability zones of neotectonic faults that have favorable conditions for the concentration of a number of elements: Mn, Cu, Ag. Such zones are characterized by the gas anomalies in sediments (methane, hydrogen, etc.). The accumulation of anomalous metal contents is facilitated by specific geological conditions that occur in zones of gas anomalies within tectonically active structures, where fine-grained sediments enriched with organic matter are present. The gas-geochemical fields formed in this pattern can be applied as indicators in forecasting of hydrocarbon accumulations, for mapping permeable fault zones, and for the environmental impact assessing of hydrocarbon anomalies. This approach could be especially effective in the basins with low seismic activity such as seas of East Siberian shelf and some of the marginal seas of Pacific Ocean, for instance, South China Sea (Bien Dong).